2018
DOI: 10.1002/adom.201800256
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Group III–V Nanowire Infrared Detectors

Abstract: Abstract1D III–V semiconductor nanowires (NWs) attract significant interests in fundamental physics and promising applications of high‐performance room‐temperature infrared (IR) detectors. Here, a comprehensive overview of recent advances in the study of III–V NW‐based IR detectors is presented, starting from the rationale of III–V NWs for IR detectors, the controllable synthesis of III–V NWs to the precise manipulation of III–V NW‐based IR detector performances. With a bandgap covering the whole IR wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 145 publications
0
39
0
Order By: Relevance
“…In this section, typical III-V single nanowire infrared photodetectors are discussed based on their device structures and operating wavelengths. The associated performance metrics such as responsivity (R), specific detectivity (D * ), gain (G), external quantum efficiency (EQE), and response time (t) [1,34] under room temperature are summarized and compared in Table 1.…”
Section: Single Nanowire Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, typical III-V single nanowire infrared photodetectors are discussed based on their device structures and operating wavelengths. The associated performance metrics such as responsivity (R), specific detectivity (D * ), gain (G), external quantum efficiency (EQE), and response time (t) [1,34] under room temperature are summarized and compared in Table 1.…”
Section: Single Nanowire Photodetectorsmentioning
confidence: 99%
“…In particular, III-V semiconductor nanowires have direct and widely tunable bandgap, high absorption coefficient and carrier mobility, as well as flexibility to form heterostructures, making them excellent candidates for photodetection [1,33]. Moreover, it is found that the enhanced photocarrier lifetime and decreased transit time in nanowire detectors lead to much higher gain in nanowires in comparison to bulk structures [34]. Researchers have also implemented transistor structures [11,[35][36][37], metal-semiconductor (M-S) or metal-semiconductor-metal (M-S-M) Schottky junctions [38][39][40][41], p-n junctions [42,43], and heterostructures [42][43][44][45][46] in nanowire-based photodetectors to further reduce dark current and enhance I light /I dark ratio for infrared photodetection.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, GaSb shows the highest hole mobility of 1000 cm 2 V −1 s −1 [36]. Figure 1(b) shows bandgaps and band alignment for the selected III-V binary semiconductors plotted as a function of the cubic lattice constant [47]. With the large lattice constants, InSb, AlSb and GaSb show narrow bandgaps compared to the other III-V semiconductors.…”
Section: The Fundamental Properties and Growth Mechanism Of Sb-basedmentioning
confidence: 99%
“…Moreover, the 1D NWs nanostructure with the large surface-to-volume ratios and Debye length typically shows superior ability of light absorption, prolonged photocarrier lifetime and shortened transit time during photoelectric processes [45,46]. Therefore, the 1D semiconductor NWs-based photodetectors facilitate highly integrated and miniature devices, showing the advantages of high responsivity, specific detectivity, fast response, high spectral selection, good flexibility, and low energy consumption [11,47,48]. In this case, both InSb and GaSb NWs have been demonstrated in the application of IR detectors in the past few years [12,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor nanowires (NWs) have attracted intense research for constructing miniaturized nanophotonic and optoelectronic devices, including passive waveguides and resonators [1][2][3], and active light-emitting devices [4][5][6], photodetectors [7], and photovoltaic devices [8]. Unfortunately, the very poor couplings between NWs and light make it difficult to realize devices with high performance [9].…”
Section: Introductionmentioning
confidence: 99%